What Are Some Common Fire Flow Requirements for Municipalities?. Issue 10 (1st October 2016) - Kelly, Kevin
Abstract : Most municipalities are willing to incur higher costs for water distribution system sizing because of the reduction in loss made possible by using the water system for fire protection. Water in sufficient quantity can cool a fire; steam can deprive the fire of oxygen, and in the case of miscible or dense fluids, water can disperse the fuel. The key question for water utilities is how large must distribution system components be to provide sufficient water for fire protection.